1998
DOI: 10.1046/j.1523-5378.1998.08035.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal PPI‐based Triple Therapy for the Cure of Helicobacter pylori Infection: A Single Center Comparison of Four 14‐day Schedules

Abstract: All PPI-based triple therapies tested in this study were effective in curing H. pylori infection; however, P + C + B resulted in rates too low (< 85%) to be recommended. P + C + A and P + A + T resulted in the high cure rates and thus may be considered the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is worthwhile pointing out that eradication rates of 75 and 64%, achieved with the 2-week and 1-week regimens, respectively, according to PP analysis, are lower than those obtained with either 1-or 2-week regimens in three European randomized controlled trials (RCT) in which rates ranging from 87 to 93% were reported [20,26,27]. The trial design could, in part, account for the limited efficacy of the treatment regimens observed in the present study, as controlled double-blind trials are generally associated with better results [28,29].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is worthwhile pointing out that eradication rates of 75 and 64%, achieved with the 2-week and 1-week regimens, respectively, according to PP analysis, are lower than those obtained with either 1-or 2-week regimens in three European randomized controlled trials (RCT) in which rates ranging from 87 to 93% were reported [20,26,27]. The trial design could, in part, account for the limited efficacy of the treatment regimens observed in the present study, as controlled double-blind trials are generally associated with better results [28,29].…”
Section: Discussionmentioning
confidence: 93%
“…At multivariate analysis, none of the pretreatment patient characteristics, that is, age, sex, and smoking habit appeared, in agreement with the two Italian studies [4,32], to be predictive of successful triple therapy. A relative homogeneity of our patients, in terms of age and low frequency (23%) of smokers, could have limited the possibility of detecting predictive factors of H. pylori eradication, as suggested by others [20,27,36]. Some authors [37,38] have reported that the frequency of H. pylori eradication is higher in patients with PUD than in those with NUD, although this evidence has not been confirmed by other investigators, probably on account of the small number of patients studied or the high overall eradication rates, as pointed out by de Boer et al [39].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thirty‐three studies were initially evaluated for meta‐analysis 12–25 ,. 28–46 Nineteen studies were excluded from further analysis 28–46 . Reasons for exclusion are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In case of missing or conflicting data, we tried to contact the authors in order to obtain the necessary data. Fourteen studies were excluded because a prospective, randomized design was lacking; 22 –35 three because the number of patients in the different treatment groups was not mentioned; 36 –38 one because it contained conflicting data; 39 and five studies because there was no clear statement that randomization was performed 40 –44 …”
Section: Resultsmentioning
confidence: 99%